2018
DOI: 10.1139/cjz-2017-0314
|View full text |Cite
|
Sign up to set email alerts
|

Movement-based methods to infer parturition events in migratory ungulates

Abstract: Long-distance migrations by ungulate species are a globally imperiled natural phenomenon and conservation of them requires monitoring population vital rates. Satellite telemetry tracking is widely used for understanding the spatial distribution and movement of animals, especially migratory animals in remote environments. Recently, analytical methods have been developed to infer parturition events from movement data in multiple species that calve in isolation, but to date such methods have not been tested on an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…We compared arrival times estimated in this study with independently estimated and validated parturition dates for the Western Arctic herd caribou (Cameron et al. , M. Cameron, E. Gurarie, K. Joly, unpublished data ), and found that parturition occurred on average 4.0 d (SD 3.4, n = 100) after the individual mean posterior arrival date. Similarly, Gunn and Poole () identified peak calving times roughly within a week of our estimated arrival times for the Bathurst herd, with 2005 identified as the latest peak calving period (14–20 June), corresponding to the latest estimated mean arrival time in our analysis (10 June).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…We compared arrival times estimated in this study with independently estimated and validated parturition dates for the Western Arctic herd caribou (Cameron et al. , M. Cameron, E. Gurarie, K. Joly, unpublished data ), and found that parturition occurred on average 4.0 d (SD 3.4, n = 100) after the individual mean posterior arrival date. Similarly, Gunn and Poole () identified peak calving times roughly within a week of our estimated arrival times for the Bathurst herd, with 2005 identified as the latest peak calving period (14–20 June), corresponding to the latest estimated mean arrival time in our analysis (10 June).…”
Section: Discussionmentioning
confidence: 95%
“…, Cameron et al. ). As the quantity of individually tracked movement data increases, hierarchical approaches to movement modeling will be increasingly relevant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations